1972
DOI: 10.1002/pssa.2210130124
|View full text |Cite
|
Sign up to set email alerts
|

Galvanomagnetic properties of CuCr2Se4

Abstract: A ferromagnetic CuCr2Se4 compound has been obtained and temperature dependences of electric conductivity, thermoelectromotive force, and the Hall effect have been measured in the temperature range from 100 to 650°K covering the magnetic‐phase transfer temperature, in order to make clear the charge transfer mechanism and the interrelation between magnetic and electrical properties. The temperature dependences of the normal and spontaneous parts of the Hall potential have been evaluated. Assumptions are made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…w 50 K) and to possess a spinel structure which undergoes peculiar 0 The purpose of this paper is to present an investigation of the temperature dependence of the electrical conductivity and thermoelectromotive force of Cu4-xMn2Te4 (-0.1 6 x 5 0.5) in a wide range of temperatures (100 to 650 K).The samples were prepared from the initial elements in an evacuated quartz ampoule at 650 C during 24 h. The analysis of the interplane distances estimated from the powder roentgenograms demonstrated that all the compositions have the spinel-typecrystallographic structure with a = 11.94 8(2). The compensation method was employed to measure the electrical conductivity, Hall effect , and thermoelectromotive force(3). 0 displays the values of the electrical conductivity and thermoelectromotive force versus x a t liquid nitrogen temperature.…”
mentioning
confidence: 99%
“…w 50 K) and to possess a spinel structure which undergoes peculiar 0 The purpose of this paper is to present an investigation of the temperature dependence of the electrical conductivity and thermoelectromotive force of Cu4-xMn2Te4 (-0.1 6 x 5 0.5) in a wide range of temperatures (100 to 650 K).The samples were prepared from the initial elements in an evacuated quartz ampoule at 650 C during 24 h. The analysis of the interplane distances estimated from the powder roentgenograms demonstrated that all the compositions have the spinel-typecrystallographic structure with a = 11.94 8(2). The compensation method was employed to measure the electrical conductivity, Hall effect , and thermoelectromotive force(3). 0 displays the values of the electrical conductivity and thermoelectromotive force versus x a t liquid nitrogen temperature.…”
mentioning
confidence: 99%